Quality Assessment of Daily Test Questions on Volleyball Game Material for Class XI at SMA N 6 Semarang - Martaningtyas, Ayu; Wiyanto, Agus; Mujiono, Eko (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objective. The objective of this investigation was to evaluate the quality of multiple-choice daily test items on volleyball game material in class XI of SMA Negeri 6 Semarang during the 2024/2025 academic year. Materials and Methods. A descriptive methodology was implemented in this quantitative investigation. The documentation method employed to gather data included examinees' responses, answer keys, and exam queries. Additionally, the anatesv4 program was employed to evaluate the quality of the questions by evaluating the efficacy of distractors, the difficulty level, and the discriminating power. Results of the item analysis at SMA Negeri 6 Semarang, Semarang City indicated that 10 questions (approximately 29 percent) were deemed to be of exceptional quality, 14 questions (approximately 40 percent) were deemed to be of good quality, 8 questions (approximately 22 percent) were deemed to be sufficient, and 3 questions (approximately 9 percent) were deemed to be of poor quality. The difficulty level of the questions was as follows: 1 question (3%) was classified as difficult, 24 questions (approximately 69 percent) were classified as moderate, and 8 questions (approximately 22 percent) were classified as The data processing results indicated that the volleyball game material had good discriminatory power, moderate difficulty, and good distractor efficacy, which was consistent with the daily tests. Conclusion. The data processing results indicate that the quality of daily test items on volleyball game material has a moderate level of difficulty, a high level of discriminating power, and a high level of distractor effectiveness